Internet access practices and employee attitudes toward internet usage policy implementation in selected Philippines financial institutions - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak Hukum UGM, 2004)
This study explores the employees' concept of appropriate use of Internet facilities as well as their perception of the rights and liabilities, both of the individual and of the organization, associated with the grant of Internet access privileges in the workplace. It further examines how employees perceive their organization's monitoring of employees online activities and the use of an Internet Usage Policy, whether these are seen as monitoring and control mechanisms or as ways to ensure that Internet access facilities are shared equitably and used responsibly. While the issue of the impact of Internet access on employee productivity will not directly be tackled, the study will provide insights into the frequency and type of usage of Internet facilities in the workplace. Considering the sizeable investment that an organization makes to provide Internet facilities, determining how employees use these facilities to achieve the goals of the organization is, in the very least, interesting and for most organizations concerned with their survival in difficult times, critically important.